Pemberian Terapi Kompres Serai Hangat pada Tn. S dengan Osteoartritis untuk Mengurangi Nyeri Sendi - Deni Pradana, Mustika; Melizza, Nur (Universitas Duta Bangsa Surakarta, 2025)
Introduction: Osteoarthritis is degenerative disease which there are pathological changes in joint structure characterized by joint cartilage damage, osteophyte growth at the joint edge, stretching of the joint capsule, inflammation, and weakening of the muscles that connect the joints. This paper work raises the case of Mr. S with osteoarthritis who has complaints of pain for 2 months. Objectives: To analyze nursing care for Mr. S with warm lemongrass compress therapy. Methods: The research method used in this paper was a case study report. The author follows the scientific method in accordance with the rules of the nursing process which includes: assessment, data analysis, nursing intervention, implementation, and evaluation. In the assessment process, the author used data collection techniques such as history taking, observation, interviews, and physical examination to collect data. Results: After analyzing patient data, 3 nursing diagnoses were raised, it was acute pain, impaired skin integrity, and risk for falls. Researcher made acute pain as priority diagnosis in this study. The provision of warm lemongrass compress therapy was able to reduce pain in Mr. S with osteoarthritis from pain scale 5 to 3. Conclusions: Acute pain nursing problems by providing interventions in the form of warm lemongrass compresses can reduce the pain scale, but do not solve the problem of joint range in patients. Range of motion recommendation therapy is needed by osteoarthritis patients in the hope of normalizing the patient's range of motion. Keyword: Nursing Care, Osteoarthritis, Joint Pain, Lemongrass Leaf.